Macrocausas da criminalidade e da violência: estudo sobre o mapeamento e diagnóstico interdisciplinar de cvlis – condutas violentas letais intencionais no rio grande do norte (2011 a 2018) - Hermes Junior, Ivenio do Espirito Santo (Universidade Federal Rural do Semi-Árido, 2019)
The research project Mapping CVLIs in Rio Grande Do Norte - From 2012 to 2018 Macrocauses of Crime and Violence produces a study on the macrocauses of violent intentional lethal conduct in Rio Grande do Norte. In this model, the mapping made specifically of these conducts in the interstice between 2011 and 2018 immerses itself in the main variables that allow these events to be plotted in the state universe, relating their condition to happen to its possible cause, within a social microuniverse of susceptibilities. The research was made on the consolidated database of OBVIO - Observatory of Intentional Lethal Violence of Rio Grande do Norte, which is the main source of consultation, since it interpolates and concatenates data through the Multifontee Platform that gathers journalistic information, Health system, the institute of expertise and the qualitative research done by OBVIO. The variables used were defined by the model proposed by the Potiguar Observatory: 1) Factual variables; 2) Sociodemographic variables; 3) Situational and social variables, and; 4) Macrocauses of homicidal crime
Keywords: Violência; Homicídio; CVLI; Mapeamento; Rio Grande do Norte; Violence; Homicide; CVLI; Mapping; Rio Grande do Norte; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES